Plastic surgery in gynaecology: Factors affecting women's decision to undergo labiaplasty. Mind the risk of body dysmorphic disorder: A review - Müllerová, Jana; Weiss, Petr (Journal of women & aging, 2020)
Aesthetic surgery of the female genitalia is on the rise. Many procedures are performed. Body dysmorphic disorder (BDD) is a psychiatric disorder and often goes unrecognized in plastic surgery. This review examines actual knowledge of plastic surgery in gynecology, knowledge of motivational factors of women, and BDD. We carried out a systematic electronic search. We used a combination of relevant keywords to construct the search strategy. Included studies were systematic reviews or primary studies published 1990-2017 and containing information about BDD. Reviewers independently assessed study eligibility, extracted data, and assessed quality, undertaking narrative synthesis. The research revealed a variety of plastic procedures available and why women consider undergoing labia reduction surgery.
Keywords: spokojenost pacientů; Plastic Surgery Procedures; Female; Patient Satisfaction; Decision Making; ženské pohlaví; Body Dysmorphic Disorders; lidé; motivational factors; tělesné dysmorfické poruchy; zákroky plastické chirurgie; Vulva; plastic surgery; female genital cosmetic surgery; představa o vlastním těle; rozhodování; Body Image; Body dysmorphic disorder; vulva; labiaplasty; Humans